Canadian Association of Paediatric Nephrologists COVID-19 Rapid Response: Home and In-Center Dialysis Guidance. (November 2021) - Alabbas, Abdullah; Harvey, Elizabeth; Kirpalani, Amrit; Teoh, Chia Wei; Mammen, Cherry; Pederson, Kristen; Nemec, Rose; Davis, T. Keefe; Mathew, Anna; McCormick, Brendan; Banks, Cheryl A.; Frenette, Charles H.; et al.
Purpose of the program: This article provides guidance on optimizing the management of pediatric patients with end-stage kidney disease (ESKD) who will be or are being treated with any form of home or in-center dialysis during the COVID-19 pandemic. The goals are to provide the best possible care for pediatric patients with ESKD during the pandemic and ensure the health care team's safety. Sources of information: The core of these rapid guidelines is derived from the Canadian Society of Nephrology (CSN) consensus recommendations for adult patients recently published in the Canadian Journal of Kidney Health and Disease ( CJKHD ). We also consulted specific documents from other national and international agencies focused on pediatric kidney health. Additional information was obtained by formal review of the published academic literature relevant to pediatric home or in-center hemodialysis. Methods: The Leadership of the Canadian Association of Paediatric Nephrologists (CAPN), which is affiliated with the CSN, solicited a team of clinicians and researchers with expertise in pediatric home and in-center dialysis. The goal was to adapt the guidelines recently adopted for Canadian adult dialysis patients for pediatric-specific settings. These included specific COVID-19-related themes that apply to dialysis in a Canadian environment, as determined by a group of senior renal leaders. Expert clinicians and nurses with deep expertise in pediatric home and in-center dialysis reviewed the revised pediatric guidelines. Key findings: We identified 7 broad areas of home dialysis practice management that may be affected by the COVID-19 pandemic: (1) peritoneal dialysis catheter placement, (2) home dialysis training, (3) home dialysis management, (4) personal protective equipment, (5) product delivery, (6) minimizing direct health care providers and patient contact, and (7) caregivers support in the community. In addition, we identified 8 broad areas of in-center dialysis practice management that may be affected by the COVID-19 pandemic: (1) identification of patients with COVID-19, (2) hemodialysis of patients with confirmed COVID-19, (3) hemodialysis of patients not yet known to have COVID-19, (4) management of visitors to the dialysis unit, (5) handling COVID-19 testing of patients and staff, (6) safe practices during resuscitation procedures in a pandemic, (7) routine hemodialysis care, and (8) hemodialysis care under fixed dialysis resources. We make specific suggestions and recommendations for each of these areas. Limitations: At the time when we started this work, we knew that evidence on the topic of pediatric dialysis and COVID-19 would be severely limited, and our resources were also limited. We did not, therefore, do formal systematic review or meta-analysis. We did not evaluate our specific suggestions in the clinical environment. Thus, this article's advice and recommendations are primarily expert opinions and subject to the biases associated with this level of evidence. To expedite the publication of this work, we created a parallel review process that may not be as robust as standard arms' length peer-review processes. Implications: We intend these recommendations to help provide the best care possible for pediatric patients prescribed in-center or home dialysis during the COVID-19 pandemic, a time of altered priorities and reduced resources.